Theoc. XIII, 5): Relectura de un epíteto - Castro de Castro, J. David (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2001)
this paper studies the sense of ________ in the teoch. 13,5. this adjetive has been connected by previous research with the epic world and the portrait of heracles as a hero. on the basis of the comparison with a pindaric pasage, this study proposes to conect the world with the erotic world . an ironic use of the world is highly probable. the hero is portrayed in a complex way that mixes not only the epic and erotics worlds,but also past and presents.